A Literature Review: Future Prophetic Leadership - Dian Retnaningdiah; Mellisa Fitri Andriyani Muzakir; Nur Ellyanawati Esty Rahayu; Reno Candra Sangaji; Tomi Agus Triono; Anas Hidayat (Universitas Negeri Semarang, 2023)
This article discusses the implementation of prophetic leadership for the future. Prophetic leadership refers to the administration applied by the Prophet Muhammad SAW. Prophetic leadership has characteristics and characters that apply religious values to employees or the community to achieve success through shared goals. This study aims to get an overview of the future of prophetic leadership. Data collection techniques and data analysis using library research with the theme of prophetic leadership in the Proquest, Jstor, Emerald, ScienceDirect, and Google Scholar databases. The findings show that prophetic leadership is very influential in social life because leaders must have a clear vision and mission, communicate with subordinates, pay attention to the community's welfare, and provide opportunities for employees to discuss ideas to achieve common goals. Prophetic leadership is very suitable to be applied in organizations and society to achieve shared prosperity